Assessment of Learner Acceptance and Satisfaction with Video-Based Instructional Materials for Teaching Practical Skills at a Distance - Donkor, Francis (International Review of Research in Open and Distributed Learning, 2011)
As video-based instructional materials become available to distance learners to learn practical skills at a distance, it is important to assess the instructional effectiveness of these materials and to understand how students respond to them. This paper is the second part of a larger exploratory study that assessed the instructional effectiveness of video-based instructional materials for teaching distance learners practical skills in block-laying and concreting and how learners respond to these instructional materials. Specifically, this paper aims to assess learners’ acceptance and satisfaction with the materials. It also aims to determine whether levels of learner satisfaction and acceptance differ according to study centres. Data were collected from 71 respondents at three study centres using a self-completion questionnaire comprising 17 Likert-type items. The data were analyzed using descriptive statistics, ANOVA, and Scheffe’s post hoc test at a 0.05 level of significance. Learners appeared positive about their learning experiences with the use of video-based instructional materials to learn practical skills at a distance as they rated highly all the items assessing their acceptance and satisfaction. Results of item-by-item ANOVA regarding learner acceptance indicated that the respondents, categorized according to study centres, exhibited similar levels of acceptance for nine of the ten items. For learner satisfaction, there were no statistically significant differences for six of the seven items. Thus, learners of different study centres exhibited about the same level of acceptance and satisfaction.